Reducing Wave Overtopping on Rubble Mound Breakwaters Using Floating Kelp Farms - Filipe Miranda; Tomás Calheiros-Cabral; Diogo Mendes; Paulo Rosa-Santos; Francisco Taveira-Pinto; Tiago Fazeres-Ferradosa (Journal of Marine Science and Engineering)
Near-surface floating kelp farms constitute a Nature-Based Solution (NBS) capable of damping incident wind-generated waves, which might be beneficial to reduce wave overtopping on maritime structures. As the global mean sea level rises, the mean wave overtopping discharge is expected to increase. The incorporation of this NBS, as a green–grey solution, might be beneficial to mitigate this effect. Physical modelling experiments with random waves have been conducted to assess the ability of this NBS to reduce the mean wave overtopping discharge on a rubble mound breakwater. Results show that while the mean wave overtopping discharge was reduced by 47% with a kelp farm length of 50 m (prototype scale), a kelp farm of 200 m achieved a reduction of 93% for the tested conditions. This reduction is mainly a function of the ratio between floating kelp farm length and incident wavelength. An idealized case study at the Port of Leixões breakwater suggests that, under storm wave conditions with return period of 2 and 5 years, floating kelp farms could maintain mean wave overtopping discharges below present levels until 2070. Thus, this study highlights the relevance of incorporating NBS with existing coastal and port defence structures as an adaptation measure to mitigate climate change effects.